2020
DOI: 10.1186/s13756-020-00757-y
|View full text |Cite
|
Sign up to set email alerts
|

Successful control of the first carbapenem-resistant Klebsiella pneumoniae outbreak in a Chinese hospital 2017–2019

Abstract: Background: Carbapenem-resistant Klebsiella pneumoniae (CRKP) is considered as a serious global threat. CRKPs occurred only sporadically in the Second Hospital of Shanxi Medical University. Our study aimed to investigate and control the first outbreak of CRKP in our hospital occurred between October 2017 and August 2019. Methods: The antimicrobial stewardship (AMS) workers have been implemented control measures properly. Clinical and epidemiological data were retrospectively collected from medical records. Car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 44 publications
1
7
1
Order By: Relevance
“…The horizontal transmission of mobile elements such as plasmids, phages, integrations, conjugate elements, and insertion elements is a key factor in the outbreak of K. pneumoniae . 27 Potron A. and colleagues found that the plasmid-mediated carbapenem-resistance gene bla OXA-232 was located on a small plasmid pOXA-232 of 6,41 bp and carried a ColE-type backbone. 4 The plasmid pOXA-232 was a non-conjugative plasmid because it could not be transferred through conjugation experiments.…”
Section: Discussionmentioning
confidence: 99%
“…The horizontal transmission of mobile elements such as plasmids, phages, integrations, conjugate elements, and insertion elements is a key factor in the outbreak of K. pneumoniae . 27 Potron A. and colleagues found that the plasmid-mediated carbapenem-resistance gene bla OXA-232 was located on a small plasmid pOXA-232 of 6,41 bp and carried a ColE-type backbone. 4 The plasmid pOXA-232 was a non-conjugative plasmid because it could not be transferred through conjugation experiments.…”
Section: Discussionmentioning
confidence: 99%
“…In Zhu et al study, in a Chinese hospital from 2017 to 2019, the first CRKP outbreak which presumably put down to cross-transmitted among patients was successfully controlled via the multimodal and multidisciplinary infection control and effective surveillance. 38 Thus, only strict prevention and effective control can be taken to commendably interdict the occurrence and rapid spread of nosocomial cross-infections.…”
Section: Discussionmentioning
confidence: 99%
“…In our case, a significant risk factor for acquiring KP-NDM-1 infection was the use of previous antibiotics, including meropenem, which was analogous to device-related infections; the use of antibiotics has also been reported as a risk factor in the medical literature ( Tian et al., 2018 ; Snyder et al., 2019 ; Kollef et al., 2021 ; Seo et al., 2021 ). Carbapenem-resistant K. pneumoniae and KP-NDM-1 can cause outbreaks ( Zhu et al., 2020 ). A report from Singapore analyzing an outbreak of NDM-1-producing Enterobacter cloacae among adults admitted to an acute hospital’s general ward showed that comorbidities and recent antibiotic use were significant risk factors ( Ho et al., 2016 ).…”
Section: Discussionmentioning
confidence: 99%